Diversification of quinazolinones by Pd-catalyzed C(sp(3))-acetoxylation - Garad, Dnyaneshwar N.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2017)
The quinazolinone ring has been exploited as a directing group for C(sp(3))-H functionalization for the first time. The proximal C-gamma(sp3)-H bonds have been oxidized by palladium-catalyzed acetoxylation reaction. Various functional groups on the quinazolinone scaffold were tolerated to provide novel quinazolinone derivatives. The use of base was found to be crucial for the mono selective acetoxylations.